Aksebilitas Sarana dan Fasilitas Sekolah Bagi Anak Berkebutuhan Khusus di SD Negeri 1 Tanjung - Atgeeta Cahya Dinary Kerlap Kemerlap; Ela Dwi Utami; Fara Dilah Umami; Hikmah Widyawati; Windi Oktaviyani (Jurnal Kependidikan, 2026)
This study aims to describe the accessibility and management of school facilities for students with special needs at SD Negeri 1 Tanjung Purwokerto. The research focuses on identifying the availability of inclusive facilities, physical accessibility, and the supporting factors that enable students with disabilities to participate comfortably in school activities. Using a descriptive qualitative approach, data were collected through direct observation of school environments and in-depth interviews with administrative staff responsible for the procurement and disposal of school facilities. Documentation in the form of photos and inventory reports was also used as supporting data. The results show that SD Negeri 1 Tanjung has provided several inclusive facilities such as wheelchairs, ramps, learning aids, and motoric development tools; however, some crucial facilities such as disability-friendly toilets are still unavailable. The study also found that the management of facilities is influenced by limited funding and the lack of specifically trained teachers for special needs education. Overall, this study highlights the importance of improving both physical accessibility and professional competence to support the successful implementation of inclusive education in elementary schools.